Decision economics : some guidelines for leaders - Oxenfeldt, Alfred R. (Crisp Pub. Menlo ParkUS, 1997)
Presents selected parts of the concepts and procedures of managerial economics designed to help executives to function. Focuses on 4 tools of managerial economics - the hierarchy of objectives; models; cost concepts, and valuations of programmes and assets. Explains how to construct the hierarchy of objectives and outlines the benefits of using it. Explains how to develop various models and provides examples of an inventory model, an input-output model, and a causal and consequence net model. Examines 3 key cost concepts viz. opportunity cost, sunk cost and intangible cost. Describes some of the methods used to forecast in the valuation exercise.